2022
DOI: 10.7554/elife.83115
|View full text |Cite
|
Sign up to set email alerts
|

Environmental response in gene expression and DNA methylation reveals factors influencing the adaptive potential of Arabidopsis lyrata

Abstract: Understanding what factors influence plastic and genetic variation is valuable for predicting how organisms respond to changes in the selective environment. Here, using gene expression and DNA methylation as molecular phenotypes, we study environmentally induced variation among Arabidopsis lyrata plants grown at lowland and alpine field sites. Our results show that gene expression is highly plastic, as many more genes are differentially expressed between the field sites than between populations. These environm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 109 publications
0
0
0
Order By: Relevance
“…By conducting a prediction using future climate projections, our modeling further suggests that the divergence between the SV- and SNP-based climatic landscapes may grow in the future, potentially as a result of SVs currently conferring adaptation to the southern environment increasing in frequency and spreading northward due to climate change. Furthermore, this analysis expects that populations track the shifting fitness optima through existing variation, but SV emergence could also increase due to climate change, as environmental stress is known to induce TE mobilization 66 , 67 , potentially providing more opportunities for SV-mediated adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…By conducting a prediction using future climate projections, our modeling further suggests that the divergence between the SV- and SNP-based climatic landscapes may grow in the future, potentially as a result of SVs currently conferring adaptation to the southern environment increasing in frequency and spreading northward due to climate change. Furthermore, this analysis expects that populations track the shifting fitness optima through existing variation, but SV emergence could also increase due to climate change, as environmental stress is known to induce TE mobilization 66 , 67 , potentially providing more opportunities for SV-mediated adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…It is now clear that environmental stress may increase the rate of single-nucleotide mutations [4] as well as structural rearrangements, 2 of 18 including transposable element (TE) movements [5]. In the last few decades, a list of studies have concluded that stress may stimulate TEs to transpose in the genome and to broaden genetic diversity [6][7][8]. Importantly, novel TE insertions (TEIs) are not randomly generated over the genome and may occur frequently in stress-responsive genes, providing connections between stress action and the occurrence of novel alleles of stress-responsive genes [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it can be speculated that perhaps high molecular plasticity in response to stress is induced during stress exposures in order to maintain the stability of performance traits, maintaining the overall fitness of an individual (Nielsen & Papaj, 2022). Additionally, changes in gene expression are more likely to be the most directly impacted factor to changes in DNA methylation levels in response to stress (Hämälä et al, 2022), with observable changes in performance and fitness traits being more complex as their expression is dependent on the additive (or non-additive) effects of gene expression (Rivera et al, 2021).…”
Section: Results Frommentioning
confidence: 99%
“…Genome size has been shown to guide the natural methylation landscape of plant species, mainly via variation in abundance of transposable elements (Alonso et al, 2015;Niederhuth et al, 2016;Seymour et al, 2014). Environmental responses in methylomes can be targeted to transposable elements (Casacuberta & González, 2013;Hämälä et al, 2022;Miousse et al, 2015a;Negi et al, 2016), which leads to the hypothesis that larger genomes express stronger methylome plasticity. A relation between genome size and methylome responses to environmental stress has, however, not yet been demonstrated.…”
Section: Supplementary Data S31: Mean Coverage Distribution Of Indivi...mentioning
confidence: 99%